2018
DOI: 10.1186/s12884-018-1883-1
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of gestational weight gain in relation to the Institute of Medicine’s recommendations by maternal body mass index in rural Pennsylvania from 2006 to 2015

Abstract: BackgroundIn 2009, the Institute of Medicine (IOM) published guidance on gestational weight gain (GWG) modified by maternal pre-pregnancy body mass index (BMI). Estimates indicate that less than half of US pregnant women have GWG within recommendations. This study examined GWG from before (2006–2009) and after (2010–2015) the release of the IOM guidance in a rural, non-Hispanic white population to assess the proportion of women with GWG outside of IOM guidance, whether GWG became more likely to be within IOM g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 17 publications
2
19
0
1
Order By: Relevance
“…All medical/obstetrical variables were categorical and included prenatal care (none, first, second or third trimester), pre‐pregnancy body mass index (BMI; underweight, normal weight, overweight, obese), rate of net gestational weight gain (inadequate, appropriate, excessive), diabetes (none, pre‐pregnancy, gestational), hypertensive disorders (none, chronic/pre‐pregnancy, or pregnancy‐associated), and asthma (yes/no). As previous studies have documented under‐reporting of maternal medical conditions on the birth certificate, ICD‐9 codes abstracted from the hospital billing records were used in conjunction with birth certificate data to define the hypertension, diabetes and asthma variables.…”
Section: Methodsmentioning
confidence: 99%
“…All medical/obstetrical variables were categorical and included prenatal care (none, first, second or third trimester), pre‐pregnancy body mass index (BMI; underweight, normal weight, overweight, obese), rate of net gestational weight gain (inadequate, appropriate, excessive), diabetes (none, pre‐pregnancy, gestational), hypertensive disorders (none, chronic/pre‐pregnancy, or pregnancy‐associated), and asthma (yes/no). As previous studies have documented under‐reporting of maternal medical conditions on the birth certificate, ICD‐9 codes abstracted from the hospital billing records were used in conjunction with birth certificate data to define the hypertension, diabetes and asthma variables.…”
Section: Methodsmentioning
confidence: 99%
“…In 48% of cases, the increase in weight was higher, and in 21% of the cases, weight gain was lower than that recommended by the US Institute of Medicine (IOM) [ 1 , 2 ]. A survey conducted between 2006 and 2015 on over 18,000 women in rural Pennsylvania showed that only 25.3% of women in this population gained weight within the recommended range – 21.3% gained an amount below and 52.9% gained an amount above the range in the IOM guidelines [ 3 ]. In a group of over 14,000 Italian women, the recommended GWG was found in 40.8%, in 30.1% of the women, GWG was lower, and in 29.1%, it was higher than the guidelines [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another source of bias in calculating GWG is the timing of the final weight measurement prior to delivery. 16,17 Ideally, the final weight should be measured as close to the delivery date as possible, and an adjustment made to account for gestational age when the final weight is not measured close to the delivery date.…”
Section: Discussionmentioning
confidence: 99%
“…For example, differences in timing of the last measured weight and delivery have been noted among women with term and preterm deliveries and among women with stillbirths. 19,21 Cut-offs of within 7 days of delivery have been applied in some studies 17 and databases, including the British Columbia Perinatal Data Registry. 19,22 However, evidence-based cutoffs for delivery weight are not established.…”
Section: The Effect Of Gestational Age On Gwgmentioning
confidence: 99%